Differences between the non-technical skills for skilled workers towards highest educational level in the electronics industry in Klang Valley, Malaysia - Md. Nasir, Ahmad Nabil (Serials Publications, 2016)
This paper discusses about the differences between Non-Technical Skills for skilled workers towards their highest educational level in the electronics industry in the Klang Valley, Malaysia. This research is a quantitative research and used questionnaire as their medium of research. There are seven of Non-Technical Skills elements that use in this research which are Communication Skills, Creative Thinking and Problem Solving Skills, Information Management Skills, Leadership and Organizational Skills, Teamwork Skills, Work Attitudes and Personal Traits and Self- Management Skills. The means of all Non-Technical Skills for skilled workers for highest education level is obtained. One-way ANOVA and Post-Hoc ANOVA Turkey are used to get the differences between the variables. In this research, there are the differences between the Non-Technical Skills for skilled workers towards their highest educational level in the electronics industry in the Klang Valley, Malaysia.